(untitled) (Ecological Bulletin of Kryvyi Rih District, 2019)
On the basis of the use of the basic provisions of the theory of ecological and taxonomic spectra, the features of the composition of ancient Mediterranean species of the group of habitats of plant groups of Kryvyi Rih dumps are deﬁned. The spectra of taxons, ecomorphs, taxonomic scope of ecomorphs and ecomorphic capacity of taxons both generic for this group of habitats and speciﬁc to certainn arealogical groups, fractions are built. The comparative analysis of the features of the ancient Mediterranean group of habitats with the composition of the polyregional group of habitats and general composition of plant group species of the study area is held.